2017
DOI: 10.1051/0004-6361/201630374
|View full text |Cite
|
Sign up to set email alerts
|

Possible quasi-periodic ejections in quasar B1308+326

Abstract: Context. The search for periodic features in flux variability and kinematics of superluminal components in blazars is capable of providing significant clues for the understanding of the physical processes in their central engines (black-hole/accretion-disk systems), especially concerning the formation and structure of their relativistic jets and radiation mechanisms. Aims. The jet swing on parsec-scales and the change of the ejection position angle of the superluminal components with time in the quasar B1308+3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 146 publications
(185 reference statements)
0
33
0
Order By: Relevance
“…In the following we apply the precessing jet nozzle model proposed by Qian et al (1991Qian et al ( , 2009 to model-fit the kinematics of the superluminal components observed in 3C279 during the period 1981-2015. This model has been applied to study the jet kinematics and precession in several blazars (e.g., 3C345, 3C454.3, NRAO 150, 3C279, B1308+326, PG 1302; see Qian 2011Qian , 2012Qian , 2013Qian , 2016Qian et al 2009Qian et al , 2014Qian et al , 2017Qian et al , 2018. The precessing nozzle model contains a number of assumptions: (1) superluminal components are ejected from the jet nozzle and move along the jet axis, which has a parabolic or helical pattern; (2) the jet axis precesses around a fixed precession axis with a certain period, sweeping a jet cone; (3) the innermost trajectories of the knots are assumed to follow a precessing common trajectory and their outer trajectory may deviate from the common trajectory pattern at different core separations, and trajectory curvatures should be taken into consideration; (4) the distribution of the isolated knots sequentially ejected at different times by the nozzle reveals the structure and evolution of the entire jet (jet-body) seen on VLBI maps.…”
Section: Working Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the following we apply the precessing jet nozzle model proposed by Qian et al (1991Qian et al ( , 2009 to model-fit the kinematics of the superluminal components observed in 3C279 during the period 1981-2015. This model has been applied to study the jet kinematics and precession in several blazars (e.g., 3C345, 3C454.3, NRAO 150, 3C279, B1308+326, PG 1302; see Qian 2011Qian , 2012Qian , 2013Qian , 2016Qian et al 2009Qian et al , 2014Qian et al , 2017Qian et al , 2018. The precessing nozzle model contains a number of assumptions: (1) superluminal components are ejected from the jet nozzle and move along the jet axis, which has a parabolic or helical pattern; (2) the jet axis precesses around a fixed precession axis with a certain period, sweeping a jet cone; (3) the innermost trajectories of the knots are assumed to follow a precessing common trajectory and their outer trajectory may deviate from the common trajectory pattern at different core separations, and trajectory curvatures should be taken into consideration; (4) the distribution of the isolated knots sequentially ejected at different times by the nozzle reveals the structure and evolution of the entire jet (jet-body) seen on VLBI maps.…”
Section: Working Assumptionsmentioning
confidence: 99%
“…Here φ represents the phase of the helical motion and A represents the amplitude. Both are functions of arc-length Geometry of the precession model, adopted and generalized from Qian et al (1991Qian et al ( , 2017Qian et al ( , 2018. Five coordinate systems are introduced.…”
Section: Formalism Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The observational evidence largely comes from two kinds of phenomena: (i) periodicities in optical and radio light curves which are correlated in some cases; (ii) periodic variations in (compact) radio cores mapped by VLBI, which include quasi-periodic undulating jet structures (swing of jet spines) and quasi-periodic wobbling of the ejection position angle of superluminal components. Many reports may be referred for several blazars, for example, BL Lac (Raiteri 2001;Stirling et al 2003;Tateyama 2009); 3C273 (Abraham & Romero 1999;Savolainen et al 2006;Calzadilla et al 2015); PKS 0420-014 (Britzen et al 2001); B0605-085 (Kudrayavtseva et al 2011); 3C279 (Qian 2012(Qian , 2013; 3C345 (Qian et al 1991;Steffen et al 1995;Qian et al 2009); 3C454.3 (Qian et al 2007(Qian et al , 2014; OJ287 (Kikuchi et al 1988;Villata et al 1998;Tateyama & Kingham 2004;Valtonen & Wiik 2012;Valtonen & Pihajoki 2013); NRAO 150 (Agudo et al 2007;Agudo 2009;Molina et al 2014;Qian 2016); PG 1302-102 (Graham et al 2015;Kun et al 2015); B2 1308+326 (Lister et al 2013;Qian et al 2017;Britzen et al 2017;hereafter BQS17). Most recently, Calzadilla et al (2015) reported the detection of the jet precession on sub-parsec scales in the archetypal blazar 3C273 with the Event Horizon Telescope at 1.3 mm wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…Their observed ejection times are ∼2005.01 ± 0.7 and ∼2007.31 ± 0.3, differing by ∼2.3 yr. If its jet swing is periodic and produced by the jet precession, then the precession period should be a bit longer than 4.6 yr (see Qian et al 2017;Britzen et al 2017 for QSO B1308+326 and below). Moreover, knot C6 and knot C1 have very similar (almost the same, see Fig.…”
Section: Introductionmentioning
confidence: 99%